ENGLISH LANGUAGE EDUCATORS’ EXPERIENCES AND PERCEIVED SUPPORT FOR AI TOOLS IN LANGUAGE TEACHING - Akhiar, Ayuni; Izhar, Nurul Ashikin; Daniel, Nurul Aziah Mohd (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
The study investigates the experiences and perceived support needed by English language educators in Malaysia when integrating AI tools into teaching practices across three instructional phases. Adopting a convergent parallel mixed-methods approach, quantitative data were gathered from 69 English educators via questionnaires and qualitative insights were obtained through semi-structured interviews with four purposefully selected educators. Guided by Abdous’s (2011) Process-Oriented Framework, the findings reveal that while educators predominantly use AI tools for lesson planning (89.9%), AI use declines substantially in the after-lesson phase (59.4%), largely due to technical challenges, insufficient training, and inconsistent institutional support. Notably, the study challenges earlier literature that characterised AI use as exploratory during lessons, instead revealing a robust in-class adoption rate of 78.3%, suggesting growing pedagogical confidence. A support-practice paradox was identified: despite perceived institutional encouragement, the absence of clear policy guidelines and inadequate infrastructure constrain meaningful AI integration. The study underscores the urgent need for comprehensive, subject-specific professional development, improved technological infrastructure, and clearer institutional guidelines to support effective and reflective AI integration across the full instructional lifecycle in Malaysian English Language Teaching.